Seismic stratigraphy of the inner to mid Agulhas bank, South Africa. (1st May 2020) - Cawthra, H.C.; Frenzel, P.; Hahn, A.; Compton, J.S.; Gander, L.; Zabel, M.
Abstract: The inner to mid continental shelf of the Agulhas Bank, which forms part of the Palaeo-Agulhas Plain, is scattered with Pleistocene deposits. Their wide lateral extension is the expression of a flat underlying substrate, availability of accommodation space, and depositional processes in response to glacio-eustatic sea-level change. We present seismic sub-bottom profiles up to 30 m deep, sediment cores up to 5 m in length and Pleistocene deposits that date back to Marine Isotope Stage (MIS) 7 from the inner to mid shelf between the Breede River in the West and Plettenberg Bay in the East. Radiocarbon and optically stimulated luminescence dates are integrated with microfossil analysis into a seismic stratigraphic model comprised of twenty Quaternary facies units within two depositional sequences bounded by shelf-wide unconformities. Sequence Boundary 1 (SB1) corresponds to the erosional unconformity with bedrock and SB2 to the MIS 2 glacial lowstand. Incised palaeo-river channels are associated with both sequence boundaries and cored deposits also mapped seismically from estuarine, lacustrine and fluvial systems are grouped to represent the lower floodplain. The most pervasive stratigraphic pattern in these shelf deposits is made up of the depositional sequence remnant of the Falling Stage Systems Tract (FSST) forced regression from MIS 5e–2. The other dominant stratigraphic group is the Transgressive Systems Tract (TST) associated with the Post-glacial Marine Transgression. The TST makes up an almost equal proportion of deposits in both sequences in the sedimentological record as the FSST, despite the shorter temporal span of the TST. A Wave Ravinement Surface marks the rise in sea level from the Last Glacial Maximum in a landward direction. Highlights: Seismic stratigraphy of the Agulhas Bank. Seismic stratigraphy of the Palaeo-Agulhas Plain. Radiocarbon dating of continental shelf marine cores. Geological evidence for Pleistocene sea-level change.